2012
DOI: 10.1007/s00441-012-1374-z
|View full text |Cite
|
Sign up to set email alerts
|

Visual photoreceptor subtypes in the chicken retina: melatonin-synthesizing activity and in vitro differentiation

Abstract: The chicken retina contains five visual photoreceptor subtypes, based on the specific opsin gene they express. In addition to the central role they play in vision, some or all of these photoreceptors translate photoperiodic information into a day-night rhythm of melatonin production. This indolic hormone plays an important role in the photoperiodic regulation of retinal physiology. Previous studies have stopped short of establishing whether melatonin synthesis takes place in all the photoreceptor spectral subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Previous studies in rat retina have revealed very faint expression of Hiomt (28), and it was virtually undetectable in bovine (51) and macaque retinas (26). Previous studies showed HIOMT immunoreactivity in IS of several mammalian [rat, bovine and human (53)] and non mammalian species [chicken (30,54) and lizard (53)] ( Table 2). In situ hybridization studies have been hampered by the lack of specific probes due to the highly divergent Hiomt sequences as demonstrated between mouse strains (52).…”
Section: Differential Expression Of Aa-nat Hiomt and Mt1 Suggests DImentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies in rat retina have revealed very faint expression of Hiomt (28), and it was virtually undetectable in bovine (51) and macaque retinas (26). Previous studies showed HIOMT immunoreactivity in IS of several mammalian [rat, bovine and human (53)] and non mammalian species [chicken (30,54) and lizard (53)] ( Table 2). In situ hybridization studies have been hampered by the lack of specific probes due to the highly divergent Hiomt sequences as demonstrated between mouse strains (52).…”
Section: Differential Expression Of Aa-nat Hiomt and Mt1 Suggests DImentioning
confidence: 91%
“…These differences indicate that control of melatonin synthesis occurs at the level of transcription in rodents, while in primates this control is principally post-translational (26). However, chicken retinas express hiomt mRNA in photoreceptors (30). HIOMT/hiomt biology is still poorly understood, partly because the level of hiomt gene expression is low and constitutive in rat retina (28), partly because HIOMT has not been detected in nonhuman primate eyes (26), and also because its sequence is extremely divergent between species (29).…”
mentioning
confidence: 99%
“…Photoreceptors are the primary source of melatonin In the retinas of vertebrates [1], [33], [43], [44] and its synthesis in these cells is controlled by the clocks harbored by these cells [1], [4], [45], [46]. We prepared re-aggregate cultures from E6 chicken retinas and exposed them to a 12L:12D cycle for six days.…”
Section: Resultsmentioning
confidence: 99%
“…; Voisin et al . ). The nature of this long time lag between commitment to a photoreceptor fate and opsin gene expression has not been elucidated.…”
mentioning
confidence: 97%
“…More recently, we observed that chicken retinal precursors isolated in culture after E10 spontaneously activate rhodopsin gene transcription (Voisin et al . ). Therefore, this study sought to examine the possible role of cAMP‐ and Ca 2+ ‐dependent signaling pathways in the spontaneous activation of rhodopsin gene transcription in chicken retinal precursors cultured after E10.…”
mentioning
confidence: 97%